Beauty, Job Tasks, and Wages: A New Conclusion about Employer Taste-Based Discrimination - Stinebrickner, Ralph; Stinebrickner, Todd; Sullivan, Paul (The Review of Economics and Statistics, 2019)
Using novel data from the Berea Panel Study, we show that the beauty wage premium for college graduates exists only in jobs where attractiveness is plausibly a productive characteristic. A large premium exists in jobs with substantial amounts of interpersonal interaction but not in jobs that require working with information. This finding is inconsistent with employer taste-based discrimination, which would favor attractive workers in all jobs. Unique task data address concerns that measurement error in the importance of interpersonal tasks may bias empirical work toward finding employer discrimination. Our conclusions are in stark contrast to the findings of existing research.